Pengaruh lama perendaman plat resin akrilik dalam ekstrak sereh wangi (cymbopogon nardus) - Edward Siyulan; Yayuk Yuliarsi (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Patients who have lost their teeth can use dentures as an alternative treatment. The use of dentures must also be followed by adequate cleaning. One of several alternative to clean dentures is to use citronella grass (Cymbopogon nardus) which contains active compounds that can reduce the growth of Candida albicans. Objective: To determine the effect of immersion duration of acrylic resin plate in citronella grass on the growth of Candida albicans. Method: The method of this study was experimental laboratory research using 27 samples of acrylic resin plates which were divided into 3 negative control groups, 3 positive control groups and 3 groups using cintronella grass extract with a concentration of 50% with an immersion time of 4 hours, 6 hours and 8 hours. Results: the group with immersion time of 4 hours, 6 hours and 8 hours showed a significant difference to the negative control group, as well as a non-significant difference to the positive control group. Conclusion: The citronella extract group with a concentraition of 50% had a significant effectiveness against the negative control group and the same effectiveness against the positive control group.